2015
DOI: 10.16949/turcomat.31338
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dynamic Geometry Software and Physical Manipulatives on Pre-Service Primary Teachers’ Van Hiele Levels and Spatial Abilities

Abstract: The purpose of the study was to compare the influence of dynamic geometry software activities and influence of the physical manipulatives and drawing activities on the spatial ability and van Hiele levels of preservice primary school teachers in a geometry course. A quasi-experimental statistical design was used in the study. The participants were 61 pre-service primary teachers in the second year of their undergraduate program in the Department of Elementary Education at Afyon Kocatepe University. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
0
16
0
3
Order By: Relevance
“…On the other hand, these instructional tools started to be compared with dynamic software emerging in line with the recent development of computer technology. A particularly popular topic of research in this sense is whether concrete models or visual models within computer software are more effective in developing spatial ability (Baki, Kösa & Güven, 2011;Karakuş & Peker, 2015).…”
Section: Tools Used In Spatial Ability Developmentmentioning
confidence: 99%
“…On the other hand, these instructional tools started to be compared with dynamic software emerging in line with the recent development of computer technology. A particularly popular topic of research in this sense is whether concrete models or visual models within computer software are more effective in developing spatial ability (Baki, Kösa & Güven, 2011;Karakuş & Peker, 2015).…”
Section: Tools Used In Spatial Ability Developmentmentioning
confidence: 99%
“…This study investigated the role of working within a CSCL environment (i.e., VMT) on middle school students' van Hiele levels of geometric thinking (both in terms of levels and scores), and looked into students' collaborative competencies while working within the VMT environment. In the previous literature, there were a number of studies that found DGS environments to be effective in developing students' geometric thinking (Abdullah et al, 2015;Abdullah & Zakaria, 2013;Karakuş & Peker, 2015;Kutluca, 2013). The results of the current study corroborated these findings showing that students' geometric thinking levels could be developed in a CSCL environment where a multi-user DGS was embedded, even when the treatment is not long.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers observed that freely sharing and discussing ideas in a learning environment affected students' learning positively (e.g., Karakuş & Peker, 2015;Kutluca, 2013). Essentially, they implied the importance of collaboration among students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations